Utiliser la série télévisée Frontera Verde pour se représenter le territoire amazonien - Benoît Bunnik (Bulletin de l’Association de Géographes Français)
The television series Frontera Verde, broadcast by Netflix since 2019, allows us to discover the territory of the Amazon to see how it is inhabited and built by its inhabitants. The discovery of an artistic work allows us to immerse ourselves through image and sound in a remote territory on which we carry representations more or less marked by exoticism and thought as a margin. This vicarious experience allows students to build geographical concepts of territory or inhabiting, to learn a phenomenological reading of the World but also to take a step back on cultural representations, notably by making a sketch of the territory of the series.